Seizing Securities in Criminal Proceedings of the Russian Federation: Theory and Practice - Sokolova, Marina; Fatyanov, Alexey; Makeev, Alexey; Blinova, Elena; Gorlova, Yulia; Alimamedov, Elmir (Jurnal Cita Hukum, 2022)
The article discusses topical issues related to the difficulties encountered by the investigator when seizing securities. The authors, on the basis of the studied criminal procedural and civil legislation, proposed to amend the Code of Criminal Procedure of the Russian Federation, solving contradictions in theory and practice. Based on the results of studying the theoretical and practical aspects of the investigator’s activities in imposing seizure of securities, a number of issues were highlighted, which were studied in detail. In addition, proposals were made to improve the current criminal procedural legislation, which will allow the investigator to optimize the activities on the application of this measure in the future in procedural coercion, both in general and in relation to certain types of securities.Keywords: Bonafide Acquirer; Criminal Proceedings; Interrogator; Seizure of Securities Penyitaan Surat Berharga dalam Proses Pidana Federasi Rusia: Teori dan PraktikAbstrakArtikel ini membahas tentang kesulitan-kesulitan yang dihadapi penyidik dalam penyitaan surat berharga. Para penulis, berdasarkan undang-undang acara pidana dan perdata yang dipelajari, mengusulkan untuk mengubah Kode Acara Pidana Federasi Rusia, memecahkan kontradiksi dalam teori dan praktik. Berdasarkan hasil kajian aspek teoretis dan praktis dari kegiatan penyidik dalam melakukan penyitaan surat berharga, beberapa hal menjadi sorotan yang dikaji secara rinci. Selain itu, diusulkan untuk memperbaiki undang-undang acara pidana saat ini, yang memungkinkan penyidik untuk mengoptimalkan kegiatan penerapan tindakan ini di masa depan dalam paksaan prosedural, baik secara umum maupun dalam kaitannya dengan jenis surat berharga tertentu.Kata kunci: Pengakuisisi Bonafide; Proses Pidana; Interogator; Penyitaan Surat BerhargaКонфискация ценных бумаг в уголовном судопроизводстве Российской Федерации: Теория и практика АннотацияВ данной статье рассматриваются трудности, с которыми сталкиваются следователи при конфискации ценных бумаг. Авторы на основе изученного уголовно-процессуального и гражданского законодательства предложили внести изменения в Уголовно-процессуальный кодекс Российской Федерации, разрешающие противоречия в теории и практике. По результатам изучения теоретических и практических аспектов деятельности следователя при конфискации ценных бумаг выделен ряд вопросов, которые подробно изучены. Кроме того, предлагается внести изменения в действующий уголовно-процессуальный закон, которые позволили бы следователям оптимизировать их дальнейшее осуществление данного деяния в условиях процессуального принуждения как в целом, так и в отношении отдельных видов ценных бумаг.Ключевые Слова: Добросовестный Покупатель; Уголовное Судопроизводство; Дознаватель; Конфискация Ценных Бумаг